Transformasi Sosial dan Nilai Agama - Ernita Dewi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Transformation is a rapid and spectacular change in religion, social, politic and culture of society. The change happens whenever a culture assimilates to another culture. As consequence, social and cultural life of receiver culture will follow to change. Before technology influences and become undivided from the life of community, traditional community was identical with agrarian. Since the machine was invented, life then turns to be consumptive individualist. Transformation may be meant either positive or negative, which is depended on the way the community live. Transformation in religion may increase perfect realisation so that people may take care more on the people in need, which is in line with religious order as Islam explains. Social transformation also could increase community’s work ethic as life now become more dynamic.